A screen for genes that influence fibroblast growth factor signal transduction in Drosophila. - Zhu, M.Y.; Wilson, R.; Leptin, M. (Genetics, 2005)
The misexpression of an activated form of the FGF receptor (FGFR) Breathless in conjunction with downstream-of-FGF-receptor (Dof), an essential signaling molecule of the FGF pathway, in the Drosophila eye imaginal discs impairs eye development and results in a rough eye phenotype. We used this phenotype in a gain-of-function screen to search for modifiers of FGF signaling. We identified 50 EP stocks with insertions defining at least 35 genes that affect the rough eye phenotype. Among these genes, 4 appear to be specific for FGFR signaling, but most of the genes also influence other signaling pathways, as assessed by their effects on rough eyes induced by other activated receptor tyrosine kinases (RTKs). Analysis of loss-of-function alleles of a number of these genes in embryos indicates that in many cases the products are provided maternally and are involved in germ cell development. At least two of the genes, sar1 and robo2, show a genetic interaction with a hypomorphic dof allele, suggesting that they participate in FGF-mediated morphogenetic events during embryogenesis.